Sociology and ideology - Ben Rafael, Eliezer (Leiden ; Boston : Brill, 2003)
Sociology in particular is the scene of heated debates about ideology. This work brings together a series of articles that throw light on selected aspects of this intricate matter by sociologists such as Boudon, Wittrock, Arnason, Touraine, Secombe, and Sternberg.
The social sciences and the two types of relativism / Raymond Boudon -- Sociology, critique and modernity: views across the European divide / Johann P. Arnason -- The decline of the social / Alain Touraine -- Sociology as a science of culture: linguistic pluralism in Australia and Belarus / Jerzy J. Smolicz and Margaret J. Secombe -- An old theme revisited: sociology and ideology / Michel Wieviorka -- Sociology and the critical reflexivity of modernity: scholarly practices in historical and comparative context / Björn Wittrock -- Divergent commitments and identity crisis / Eliezer Ben-Rafael and Yitzhak Sternberg.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Sociology -- Philosophy; Sociologie -- Philosophie; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; Sociology -- Philosophy; Soziologie; Ideologie; Aufsatzsammlung; Sociologie -- Philosophie; Anthropologie